Examining Human Rights Abuses on Religious, Cultural, and Political Intolerance in Nigeria - Aidonojie, Paul Atagamen; Ismaila, Hassan; Eregbuonye Obieshi; Omobolanle Omolola Ikpotokin (Lembaga Contrarius Indonesia, 2025)
Over the years the concept of human rights has gained global recognisition and both the international community and Nigeria have taken necessary legal steps to secure the rights of every individual from any form of abuse. However, despite this measure, there seems to be a high rate of human rights abuse in Nigeria often necessitated by several factors. Hence, the need for this study to examine the factors often resulting in high levels of human rights abuse in Nigeria. The study adopts a doctrinal method of study relying on primary and secondary sources of research material such as laws and scholarly literature. The data obtained were analysed through descriptive and analytical methods of research. The study found that there are laws in Nigeria that tend to prohibit human rights abuse, however, there seems to be a high level of human rights intolerance resulting in human rights abuse. The study further found that religious, cultural, and political intolerance are the major causes of human rights intolerance resulting in human rights abuse. The study further concludes and recommends that resolving the issues of human rights intolerance resulting in human rights abuse requires enhanced public awareness through advocacy and education, religious and cultural reorientation on the need to respect human rights. Furthermore, there is a need to ensure political accountability, and transparency, curtail the incidence of corruption, and the establishment of independent monitoring bodies to safeguard human rights.